Comparison Of Double Disc Diffusion Method and Vitek 2 Compact System to Screen the ESBL Producers in Intensive Care Unit in Hospital - Shah, Kinal; Shrimali, Gaurishanker; Mulla, Summaiya (National Journal of Community Medicine, 2016)
Background: It is essential to develop screening methods for the detection of Extended Spectrum of B- Lactamase (ESBL) producing strains in the laboratories, so that the appropriate medication can be started. In this study we compared the ESBL strain detection with the help of double disk diffusion method and Vitek 2 compact (Biomerieux India Pvt. Ltd.). Material and Methods: 67 clinical isolates of E. coli (33) and Klebsiella spp. (34) were isolated from the intensive care unit of the hospital from India and screened for ESBL production by double disc diffusion method and Vitek 2 compact system (fully automated susceptibility testing and identification system). Results: Total 67 isolates of E. coli and Klebsiella spp. were screened in this study, out of that 16 isolates E. coli (9) and Klebsiella (7) were ESBL non-producer according to double disk diffusion method, and then these 16 isolates were retested by Vitek 2 compact system. Out of these16, 14 were ESBL non-producer E. coli (7) and Klebsiella (7) and 2 were ESBL producer by Vitek 2 compact. Conclusion: From the above results we can conclude that Vitek 2 compact is an automated system and gives more accurate results than double disk diffusion method.